Pleural Tuberculosis Mimicking Inflammatory Pseudotumour - Arul P. (Journal of Clinical and Diagnostic Research, 2013)
A pseudotumour is a rare presentation of bronchopulmonary tuberculosis which occurs in immunocompetent patients, which can simulate malignancy, both clinically and radiologically, and may cause delay in its diagnosis and treatment. The incidence of bronchopulmonary pseudotumours was found to vary from 2-4%, as was seen in various studies. A mycobacterial pseudotumour of the pleura is a rare entity. We are reporting a case of a pleura based tubercular pseudotumour in a 59 years old patient who presented with a four month history of the nonspecific symptoms of cough and chest pain. The radiological investigations showed that a pleural based mass lesion was occupying the right lower hemithorax. The initial biopsy was suggestive of a hyalinizing variant of an inflammatory pseudotumour. The follow-up surgical resected mass was consistent with the features of a tubercular granuloma. The clinical presentation and the histopathological findings have been presented, with a brief review of the literature. Due to its varied and unusual presentation, bronchopulmonary tuberculosis should always be kept in mind when a patient with a similar clinical and a radiological picture is being evaluated.